2002
DOI: 10.1106/104538902030340
|View full text |Cite
|
Sign up to set email alerts
|

Development of ER Brake and its Application to Passive Force Display

Abstract: Force display systems are important in virtual reality and other applications. While conventional force displays are active systems with actuators and as such may become inherently dangerous, passive force displays are effective methods for assuring safety. In this paper, we developed a brake using electrorheological (ER) fluid, and showed a passive force display system using ER brakes with two degrees of freedom. We also discuss basic control experiments of the system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(21 citation statements)
references
References 5 publications
0
21
0
Order By: Relevance
“…Kikuchi et al developed a new practical haptic device 'PLEMO-P1'; this system adopted ER brakes as its force generators [8]. Furusho et al developed an ER brake and showed a passive force display system using ER brakes with two degrees of freedom [9]. However, these researches were conducted by using 1-DOF ER brake.…”
Section: Introductionmentioning
confidence: 99%
“…Kikuchi et al developed a new practical haptic device 'PLEMO-P1'; this system adopted ER brakes as its force generators [8]. Furusho et al developed an ER brake and showed a passive force display system using ER brakes with two degrees of freedom [9]. However, these researches were conducted by using 1-DOF ER brake.…”
Section: Introductionmentioning
confidence: 99%
“…We can control the brake torque form 0. Figure 25 shows a passive force display using ER brakes (IEEE Virtual Reality 2001) in previous research (Furusho, Sakaguchi et al, 2002). In the research, we established control methods with a passive force display system on 2-D space.…”
Section: Er Brakementioning
confidence: 99%
“…By taking advantages of these characteristics, ER suspensions have been applied to robots for upper limb rehabilitation and so on. [10][11][12][13] In addition, these suspensions are expected to be applies in a wide range of fields.…”
Section: Suspensions Of Polarizable Particles Dispersed In Insulationmentioning
confidence: 99%